PROPOSTA DE SÍNTESE ONE-POT: PRÁTICAS EXPERIMENTAIS DE QUÍMICA ORGÂNICA E MEDICINAL A PARTIR DA PREPARAÇÃO DO HETEROCICLO TIAZOL - Arlan de Assis Gonsalves; Victória Laysna dos Anjos Santos; Sidney Silva Simplicio; Délis Galvão Guimarães; Cleônia Roberta Melo Araújo (Química Nova)
In this work we explore some theoretical and practical aspects of one-pot synthesis. The focal point of the study is the preparation of the thiazole heterocycle, with an emphasis on theoretical aspects of the organic and medicinal chemistry of this important privileged structure. The entire set of experimental procedures and characterization steps explored in this work has the potential to assist in the training and/or technical improvement of undergraduate students, and contribute to the teaching of chemistry in Brazilian higher education. It is worth emphasizing these aspects because the experiments shown in the proposed practices involve simple, rapid, low-risk, and low-cost procedures, making it perfectly feasible to reproduce them in undergraduate classes, even in laboratories with limited material resources.